Aqueous Phase Exfoliating Quasi‐2D CsPbBr3 Nanosheets with Ultrahigh Intrinsic Water Stability. Issue 34 (28th June 2019) - Xie, Meilin; Liu, Huan; Chun, Fengjun; Deng, Wen; Luo, Chao; Zhu, Zhihao; Yang, Min; Li, Yongmei; Li, Wen; Yan, Wei; Yang, Weiqing
Abstract: All‐inorganic cesium lead halide perovskite nanocrystals (NCs) have emerged as attractive optoelectronic materials due to the excellent optical and electronic properties. However, their environmental stability, especially in the presence of water, is still a significant challenge for their further commercialization. Here, ultrahigh intrinsically water‐stable all‐inorganic quasi‐2D CsPbBr3 nanosheets (NSs) via aqueous phase exfoliation method are reported. Compared to conventional perovskite NCs, these unique quasi‐2D CsPbBr3 nanosheets present an outstanding long‐term water stability with 87% photoluminescence (PL) intensity remaining after 168 h under water conditions. Moreover, the photoluminescence quantum yields (PLQY) of quasi‐2D CsPbBr3 NSs is up to 82.3%, and these quasi‐2D CsPbBr3 NSs also present good photostability of keeping 85% PL intensity after 2 h under 365 nm UV light. Evidently, such quasi‐2D perovskite NSs will open up a new way to investigate the intrinsic stability of all‐inorganic perovskites and further promote the commercial development of perovskite‐based optoelectronic and photovoltaic devices. Abstract : The quasi‐2D perovskite nanosheets obtained by an aqueous phase exfoliation method present long‐term intrinsic water stability compared to conventional perovskite quantum dots. These unique quasi‐2D perovskite nanosheets remain with 87% photoluminescence (PL) intensity after dispersing in water for 168 h.